Kinerja ESG di Negara Berkembang: Dampak Tata Kelola dan Kinerja Keuangan pada Perusahaan - Fajar Kholillulloh; Fuad Hudaya Fatchan; Bella Ananda Chairunnisa (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Sustainability has increasingly become a central concern in the global business landscape, marked by a heightened focus on Environmental, Social, and Governance (ESG) performance as an indicator of corporate responsibility and long-term value. This study aims to analyze the influence of corporate governance and financial performance on ESG performance among companies listed on the Indonesia Stock Exchange. The research utilizes secondary data derived from annual and sustainability reports during the 2020–2022 period. The findings indicate that an effective governance structure and sound financial condition can enhance a company’s commitment to sustainable business practices. The novelty of this study lies in the integration of two internal aspects—corporate governance and financial performance—into a single ESG analytical framework, distinguishing it from previous studies that examined these factors separately. The focus on companies in developing country context provides valuable contributions to the ESG literature, which has predominantly centered on developed markets.